Effect of side-dressing nitrogen in irrigated wheat after soybean in cerrado soil - da Silva, Dijalma Barbosa (Pesquisa Agropecuaria Brasileira, 1991)
Two field experiments were carried out at Planaltina, DF, Brazil, to study the effect of side-dressing N in irrigated wheat c.v. BR 12-Aruanã. The experimental site was in a Dark-Red Oxisol, where a soybean-wheat succession had been carried out for the last three years. The spacings used in these experiments were: 0,17 x 0,17 m and 0,17 x 0,34 m. Twenty kg of N/ha were applied at the sowing time. The experimental design was a complete randomized block with four replications. The treatments were: 0, 20, 40, 80 and 120 kg of N/ha applied at tillering stage in the form of urea. The effect of N did not present difference in grain yield in the experiment with 0,17 m x 0,34 m spacing. N gave a negative response in the 0,17 m x 0,17 m according to the equation: Y = 5.398,7263 - 7.8466 N, and R2 = 0,91**. Increase of N rates reduced leaf necrosis and increased lodging.